User Experience in Instructional Video: A Systematic Review - Putra Prabawa, Dewa Gede Agus; Agustini, Ketut; Dantes, Gede Rasben; Divayana, Dewa Gede Hendra (Journal of Engineering Education Transformations, 2026)
Instructional videos are content that is often used in learning. Not much research has analyzed the factors that influence user experience in using instructional videos. The purpose of this study is to determine the factors that must be considered to provide a good user experience. The research method used is the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) model. The articles reviewed are Scopus indexed in the 2018-2023 range and use the Publish or Perish (PoP) application. The results showed that 16 relevant articles out of 262 used the keywords user experience in instructional video, design learning video, design instructional video, and length of learning video. Based on the analysis of 16 articles, user experience in instructional videos relates to cognitive, satisfaction (emotional), and interactivity aspects. The principle of applying multimedia can reduce the audience’s cognitive load in listening to video messages. The video duration considered effective is a short video that is less than 6 minutes. Video interactivity can be realized by applying generative principles in the form of presenting quizzes or questions during or after the presentation of the video. Research findings show that in order for the audience’s experience to be more meaningful when watching videos, it is necessary to pay attention to the audience’s cognitive capacity, satisfaction, and interactive activities (stimulus from the video).